Tanggung Jawab Sosial Perusahaan dalam Bisnis Islam - Yuni Mayanti; Rani Putri Kusuma Dewi (Journal of Applied Islamic Economics and Finance, 2021)
This paper discusses corporate social responsibility in Islamic business or commonly known as CSR. The writing of this paper uses a qualitative descriptive method with a literature study approach by taking references from reliable sources and books and then the authors develop. This paper finds that corporate social responsibility in Islamic business has different principles from conventional business even though both have the same goals. Thus, it is deemed necessary to continue to carry out deeper studies in order to find out the company's responsibility in doing Islamic business which is very applicable in a company and can assist the company in improving the company's performance and optimal growth.